AKTIVITAS ANTIOKSIDAN FRAKSI-FRAKSI MODEL DARI PRODUK REAKSI MAILLARD (Jurnal Teknologi Pangan, 2013)
The  oxidative  browning  is  considered  to  have  a  contribute  to  the  flavor,  antioxidative activity  and  color  of  food.  As  a  result  of  this  Maillard  reaction,  a  variety  of  by  products, intermediates and brown pigmens (melanoidins) are produced. The objectives of this research was to study the effect of heating and sugar addition of Model to  antioxidant activity.  The  research is model  system of  Maillard  reaction  products  were  too  made  from  sugar and  amino  acids  and  adjusted  to  the  soysauce  preparation. The  model  contents  of  glucose – glycine - cysteine; glucose – glycine – cysteine - phenylalanine; glucose – glycine – cysteine – phenylalanine – isoleucine - tyrosine. The model were fractionated into molecular weight of 10 kDa –  100  kDa  by  ultrafiltration.  The  fractions  were  characterized  by    spectra  profile  of ultraviolet-visible. The antioxidant of fractions activity was evaluated by rancimat, DPPH(1,1-diphenyl-2-picrylhydrazyl),  TBA  value,  ferric  thio  cyanate and  hemolysis  of  erythrocyte methods.  The fractions of model can retard oxidation of oil and had DPPH radical of scavenging activity especially both Fractions  molecular weight >100 kDa (F1) and  30-100 kDa (F2), and equal  with  the  BHT  antioxidant.  Antioxidant  activity  of  glucose-glycine-cysteine model  by rancimat and thio cyanate method showed  the longest induction period for 15 hours and 72% antioxidant activity, whereas the radical DPPH scavenger activity for all model showed most equaly (60%). The fractions with molecular weight about 30-100 kDa (F2) resulted the highest antioxidant activity. The fractions of model had antioxidant activity in food and biology system.Key Words : Maillard Reactions, Model, fractinationated, antioxidative activity